Criminological Aspects of Residivis in use Narcotics - Magfirah Rahmalia Daud (Universitas Negeri Gorontalo, 2022)
The purpose of this study is to find out and analyze the criminological factors behind recidivists in narcotics use in Gorontalo Province and to find out how. The type of research used is empirical research, using primary and secondary data sources. Using data clotting techniques with observation methods, interview methods, and documentation methods. Then the data is analyzed descriptively or provides an overview or exposure to the subject and object of study as the results of the research carried out. The results showed criminological factors behind recidivist use in narcotics use in Gorontalo Province when viewed from the Differentia Associationtheory, namely environmental/social factors causing a person to commit criminal acts repeatedly. The bad stigma that arises from the society of ex-convicts makes these ex-convicts feel excluded explained based on label theory, imitation theory is the result of imitation of crimes that occur in their environment, self-defense theory is health caused by weak self-defense against their poor environment as drug users, Criminoloids theory of crimes caused by lust.